Imaginary communities : utopia, the nation, and the spatial histories of modernity - Wegner, Phillip E., 1964- (Berkeley : University of California Press, 2002)
Drawing from literary history, social theory, and political critique, this far-reaching study explores the utopian narrative as a medium for understanding the social space of the modern nation-state. Considering the narrative utopia from its earliest manifestation in Thomas More's sixteenth-century work Utopia to some of the most influential utopias of the late nineteenth and twentieth centuries, this book is an astute study of a literary genre as well as a nuanced dialectical meditation on the history of utopian thinking as a quintessential history of modernity. As he unrave.
Introduction: The Reality of Imaginary Communities -- Genre and the Spatial Histories of Modernity -- The Institutional Being of Genre -- Space and Modernity -- Estrangement and the Temporality of Utopia -- Utopia and the Birth of Nations -- Reauthoring, or the Origins of Institutions -- Utopiques and Conceptualized Space -- Crime and History -- Utopia and the Nation-Thing -- Utopia and the Work of Nations -- Writing the New American (Re)Public: Remembering and Forgetting in Looking Backward -- Remembering -- The Contemporary Cul-de-Sac -- Fragmentation -- Consumerism and Class -- "The Associations of Our Active Lifetime" -- Forgetting -- The Occluded Future: Red Star and The Iron Heel as "Critical Utopias" -- Red Star and the Horizons of Russian Modernity -- The Long Revolution of The Iron Heel -- "Nameless, Formless Things" -- "Gaseous Vertebrate" -- Simplification and the New Subject of History -- A Map of Utopia's "Possible Worlds": Zamyatin's We and Le Guin's The Dispossessed -- Reclaiming We for Utopia -- The City and the Country -- Happiness and Freedom -- The Play of Possible Worlds -- We's Legacy: The Dispossessed and the Limits of the Horizon -- Modernity, Nostalgia, and the Ends of Nations in Orwell's Nineteen Eighty-Four -- From Utopian Modernism to Naturalist Utopia -- Orwell and Mannheim: Nineteen Eighty-Four as "Conservative Utopia" -- The Crisis of Modern Reason -- Modernization against Modernity: The Culture Industry and "Secondary Orality" -- "If there was hope ... ": Orwell's Intellectuals.
Includes bibliographical references (p. 229-286) and index.
Print version record and CIP data provided by publisher; resource not viewed.
JSTOR
Keywords: Orwell, George, -- 1903-1950 -- Criticism and interpretation; More, Thomas, -- Saint, -- 1478-1535.; Orwell, George, -- 1903-1950; Utopia (More, Thomas, Saint); American fiction -- History and criticism; Utopias in literature; Comparative literature -- American and Russian; Comparative literature -- Russian and American; Russian fiction -- History and criticism; Modernism (Literature) -- United States; Modernism (Literature) -- Great Britain; Modernism (Literature) -- Russia; Space and time in literature; Nationalism in literature; Communities in literature; Utopias; Utopias; Roman américain -- Histoire et critique; Utopies dans la littérature.; Roman russe -- Histoire et critique; Modernisme (Littérature) -- États-Unis.; Modernisme (Littérature) -- Grande-Bretagne.; Modernisme (Littérature) -- Russie; Nationalisme dans la littérature.; Communauté dans la littérature.; Utopies; utopian literature; TRAVEL -- Special Interest -- Literary; LITERARY CRITICISM -- General; LITERARY CRITICISM -- Semiotics & Theory; American fiction; Communities in literature; Comparative literature -- American and Russian; Comparative literature -- Russian and American; Modernism (Literature); Nationalism in literature; Russian fiction; Space and time in literature; Utopias in literature; Great Britain; Russia; United States; Bellettrie; Utopieën.; Modernisme (cultuur); 16th century; 19th century; 20th century; criticism; critique; cultural history; cultural studies; ernst bloch; gilles deleuze; henri lefebvre; homi bhabha; jurgen habermas; karl mannheim; literary criticism; literary history